Type 2 Pfeiffer syndrome. Report of a case and review of the literature - Roldán Arce Jorge; Villarroel Cortés Camilo (Instituto Nacional de Pediatría, 2014)
Pfeiffer syndrome is a rare autosomal dominant disease that affects almost 1 out of every 100,000 live newborns, and it is associated with craniosynostosis, broad and deviated thumbs and big toes, and partial syndactyly in hands and feet. Three types of this syndrome have been described based on the presence of other abnormalities and the severity of the condition. "Classic" type 1 consists of mild severity with normal to near-normal intelligence and generally a good prognosis. Type 2 is characterized by a cloverleaf skull, severe proptosis, elbow ankylosis or synostosis, growth retardation and life-threatening neurological and respiratory complications. Type 3 is similar to type 2 but without the cloverleaf cranium. This syndrome is genetically heterogeneous, it is caused by mutations in the fibroblast growth factor receptor genes FGFR- 1 or FGFR-2. Occasionally Pfeiffer syndrome can be diagnosed prenatally by sonography or molecularly if the causative mutation is known. Management must be multidisciplinary and it includes multiple-staged surgery. In this report we present the clinical and radiographic findings in female newborn, whose clinical features were consistent with Pfeiffer syndrome type 2. A brief updated review of the literature is included.